Enhancing Tetrahydrocannabinol’s Therapeutic Efficacy in Inflammatory Bowel Disease: The Roles of Cannabidiol and the Cannabinoid 1 Receptor Allosteric Modulator ZCZ011 - Thapa, Dinesh; Patil, Mohan; Warne, Leon N; Carlessi, Rodrigo; Falasca, Marco (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: Current inflammatory bowel disease (IBD) treatments focus on symptomatic relief, highlighting the need for innovative approaches. Dysregulation of the cannabinoid 1 (CB1) receptor, part of the endocannabinoid system, is linked to colitis. While tetrahydrocannabinol (THC) alleviates colitis via CB1 activation, its psychotropic effects limit clinical use. ZCZ011, a CB1R allosteric modulator, and cannabidiol (CBD), a non-psychoactive cannabinoid, offer alternatives. This study investigated combining sub-therapeutic THC doses with ZCZ011 or CBD in a murine model of dextran sodium sulphate (DSS)-induced colitis. Methods: Acute colitis was induced with 4% DSS for 7 days, followed by 3 days of water. Chronic colitis was modelled over 24 days with alternating DSS concentrations. The combination of 2.5 mg/kg THC with 20 mg/kg ZCZ011 or 10 mg/kg CBD was evaluated. Key markers were assessed to determine efficacy and safety, including disease activity index (DAI), inflammation, cytokine levels, GLP-1, and organ health. Results: DSS-induced colitis resulted in increased DAI scores, cytokines, organ inflammation and dysregulation of GLP-1 and ammonia. THC at 10 mg/kg significantly improved colitis markers but was ineffective at 2.5 and 5 mg/kg. ZCZ011 alone showed transient effects. However, combining 2.5 mg/kg THC with either 20 mg/kg ZCZ011 or 10 mg/kg CBD significantly alleviated colitis markers, restored colon integrity and reestablished GLP-1 homeostasis. This combination also maintained favourable haematological and biochemical profiles, including a notable reduction in colitis-induced elevated ammonia levels. Conclusions: This study demonstrates the synergistic potential of low-dose THC combined with CBD or ZCZ011 as a novel, effective and safer therapeutic strategy for ulcerative colitis.